Awareness of infaq practices in Kampung Cheras Bharu, Kuala Lumpur / Amirul Aqiel Mohd Ramli - Mohd Ramli, Amirul Aqiel (Universiti Teknologi MARA, Selangor, Puncak Alam Campus, 2018)
Many of muslims in our community misunderstood or didn’t knew more clearly about the infaq knowledge and their impact to our society. Aim for this research is to evaluate the level awareness of infaq practices and their roles in our society from the area of Kg. Cheras Bharu, Kuala Lumpur. Author used survey method and field study locating method for complething this research and anlyzing the data by using SPSS. Resulting in, most of the community of Kg. Cheras Bharu understood most of the infaq practices and applying it as their customary practice frequently.